Pertanggungjawaban Pidana Penyelenggara Negara Dalam Tindak Pidana Suap Berdasarkan Undang-Undang Pemberantasan Tindak Pidana Korupsi - Hasani, Achmad Rizky (2025)
State administrators are officials involving the executive, legislative and judiciary as well as other officials whose duties are related to state administrators such as governors, judges or other officials whose duties are to comply with the principles of state violations. Bribery is an extraordinary crime which in terms of overcoming it must be done together. The occurrence of bribery can be seen as a problem that exists within state administrators. State administrators commit acts of abusing their authority in carrying out their duties contrary to the laws and regulations in force in Indonesia. The research method used is the normative legal research method. The results of the study indicate that 1) weak state supervision of the crime of bribery. 2). Weakness of state administrators in carrying out their duties from the state. 3) A culture of corruption that has become a habit in society.